Serial right ventricular assessment in patients with hypoplastic left heart syndrome: a multiparametric cardiovascular magnetic resonance study. (29th May 2021) - Sobh, Mohamed; Freitag-Wolf, Sandra; Scheewe, Jens; Kanngiesser, Luca M; Uebing, Anselm S; Gabbert, Dominik D; Voges, Inga
Abstract:  : OBJECTIVES: The aim of this study was to assess single right ventricular (RV) function in a large cohort of hypoplastic left heart syndrome (HLHS) patients after the completion of total cavopulmonary connection by analysing serial cardiovascular magnetic resonance (CMR) studies. METHODS: CMR studies from 95 HLHS patients were analysed. RV end-diastolic and end-systolic volumes (RVEDV, RVESV), ejection fraction (RVEF) and long-axis strain (LAS) were measured from cine images. RESULTS: All 95 patients had at least 2 CMR scans and 35 patients had 3 CMR scans. The median age (first quartile–third quartile) at the 3 examinations was 4.2 (3.3–6.1), 9.4 (6.1–11.4) and 14.6 (11.8–16.8) years. RV indexed volumes (RVEDVi and RVESVi) increased from first to the second and from the first and second examination to the third examination in patients with >10 years of age ( P  < 0.05). There was a slight decrease in RVEF and LAS throughout the examinations, but this was not statistically significant. Correlations were found between RVEF and LAS ( r  = −0.23; P  < 0.01). Both RVEF and LAS correlated with RVEDVi and RVESVi ( r  = −0.17 to 0.43; P  < 0.05). CONCLUSIONS: Serial assessment of CMR studies in HLHS patients after total cavopulmonary connection completion demonstrate an increase in indexed RV volumes in older HLHS patients but only mild reduction in RVEF and LAS. The correlation of indexed RV volumes with RVEF and LAS together with the significant increase in RV volumes over time suggests that indexed RV volumes might be superior to RV functional markers to monitor the RV in HLHS patients. Abstract : Hypoplastic left heart syndrome (HLHS) is one of the most severe form of congenital heart disease and is characterized by hypoplasia of the left ventricle, mitral valve and aortic valve atresia or stenosis as well as hypoplasia of the ascending aorta [1].